(untitled) (Research, Society and Development, 2020)
SARS-CoV-2 is part of an RNA virus family described again in 2019, causing the Covid-19 disease. The integration of computational strategies is of great importance in the identification and development of promising new compounds. Atazanavir and Darunavir, were designed to combat resistance to mutant drugs mainly by increasing the number of polar interactions with the main atoms in the HIV protease chain. This study aims to assess the molecular interaction of the drugs Atazanavir and Darunavir with the main SARS-CoV-2 protease through docking and molecular dynamics studies. This is a descriptive, experimental study with a qualitative and quantitative approach on the subject. For that, using the programs BIOVIA Discovery Studio, PyMol, AutoDock Tools 1.5.6, AutoDock Vina, the modeling and simulation of the anchoring of the drug at the action site were carried out. Lower scores were demonstrated, with -7.0 (Darunavir) the closest to the UAW 247 Inhibitor. It is possible to notice that the drugs showed similar residual bonds, also, in relation to the protease structure, the closest tested molecule was Atazanavir. Taking into account the stability of the RMSD values, it is valid to infer that in relation to the UAW 247 inhibitor, the drug Atazanavir is the one that best resembles, unlike Darunavir, which presents greater variations. The two drugs fit into the binding site mainly due to electrostatic interactions and hydrogen bonds. Atazanavir is the most similar to molecular activity, and Darunavir is the one with the best anchoring score.